7.4.7. Serpulidae Rafinesque, 1815 - Kupriyanova, Elena K; Rzhavsky, Alexander V.; ten Hove, Harry A. ([book chapter], 2019)
None
World Polychaeta Database (WPolyD). World Polychaeta Database (WPolyDb)